Density and Community Structure of Terrestrial Insects in an Integrated Agricultural Laboratory in Jagan, Sukoharjo, Indonesia - Vallery Armania; Anwari Adi Nugroho (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Terrestrial insects play an important role in maintaining the balance of agricultural ecosystems, studies specifically examining their community structure in educational agroecosystems, such as integrated agricultural laboratories, remain limited, thereby highlighting the need to assess their density and ecological indices as indicators of environmental conditions. The study aimed to measure the density, diversity index, richness index, evenness index, and dominance index of terrestrial insects using twelve pitfall traps at the Jagan Sukoharjo Integrated Agricultural Laboratory. The study used the pitfall trap method with twelve traps placed randomly in the study area. Observations were made for 3 consecutive days. The data collected consisted of the number of individuals of each type of terrestrial insect, which were then analyzed using density, diversity, richness, evenness, and dominance indices. The results indicate that the Integrated Agricultural Laboratory of Jagan supports a relatively high richness of terrestrial insect species; however, the community structure is still dominated by a few opportunistic species, reflecting the characteristics of an educational agroecosystem with a moderate level of ecological stability. These findings indicate that the terrestrial insect community at the Jagan Integrated Agricultural Laboratory is diverse and has the potential to reflect the ecological conditions of the local agricultural environment. Furthermore, this study provides empirical evidence that strengthens the use of terrestrial insects as bioindicators in educational agroecosystems and contributes to the development of sustainable agroecosystem management strategies through biodiversity-based monitoring.